Degradation of p27(Kip) cdk inhibitor triggered by Kaposi's sarcoma virus cyclin-cdk6 complex. - Ellis, M; Chew, Y; Fallis, L; Freddersdorf, S; Boshoff, C; Weiss, R; Lu, X; Mittnacht, S (1999)
The Kaposi's sarcoma-associated human herpesvirus 8 (KSHV/HHV8) encodes a protein similar to cellular cyclins. This cyclin is most closely related to cellular D-type cyclins, but biochemically it behaves atypically in various respects. Complexes formed between the viral cyclin and the cyclin-dependent kinase subunit, cdk6, can phosphorylate a wider range of substrates and are resistant to cdk inhibitory proteins. We show here that the KSHV-cyclin-cdk6 complex phosphorylates p27(Kip) on a C-terminal threonine that is implicated in destabilization of this cdk inhibitor. Expression of the viral cyclin in tissue culture cells overcomes a cell cycle block by p27(Kip). However, full cell-cycle transit of these cells appears to depend on C-terminal phosphorylation of p27(Kip) and seems to involve transactivation of other cellular cyclin-dependent kinases. A p27(Kip)-phosphorylating cdk6 complex exists in cell lines derived from primary effusion lymphoma and in Kaposi's sarcoma, this indicating that virally induced p27(Kip) degradation may occur in KSHV-associated tumours.